Clinical nurses' legal roles, challenges, and responses to enabling legislation in China: a qualitative study - Xiaolong Wang; Huipeng Xiao; Yufei Xing; Weichao Yuwen; Jiajia Yu; Shuhui Shang; Enming Zhang; Zhengyue Dai; Qiong Fang (BMC, 2024)
Abstract Background With the surge in China's registered nurse population, defining their rights and responsibilities is crucial for ensuring the quality of medical services. However, challenges such as unresolved medical disputes and unclear duties persist due to the inadequacy and lack of transparency in current nursing laws and policies. This study evaluated nurses' legal awareness, legislative needs, and views on laws and policies affecting their practice, providing insights for future improvements in nursing legislation. Methods This study employed a descriptive qualitative approach, utilizing purposive sampling to select 16 nurses for in-depth exploration of their experiences. Semi-structured interviews were conducted between December 2023 and March 2024. Data analysis was performed using directed content analysis. Results A total of 16 nurses with various positions and titles were interviewed. The analysis revealed three main themes and nine sub-themes, focusing on existing issues in the nursing environment, legal training needs, and attitudes towards legislative empowerment. Conclusions In China, there is a gap in legal knowledge and training among nurses. Enhancing their legal literacy is crucial for elevating their professional status and the quality of their work. Our findings underscore strong support for the enactment of the Nurse Act with a focus on practice conditions, rights protection, and career development. National authorities and experts must expedite this legislation to safeguard the rights of nurses, bolster their professional confidence.